Persistence of anti-rabies neutralizing antibodies in a rural amazonian community vaccinated with purified vero cell rabies vaccine (pvrv) following vampire bat rabies outbreak - Medeiros, R.; Maestri, A.; Le Guern, A. S.; Martorelli, L.; Almeida, M.; Kataoka, A.P. de A.G.; Houillon, G.; Jusot, V.; Zocchetti, C.; Bosch Castells, V.; Rasuli, A.; Chteoui, M.; et al. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Human rabies transmitted by vampire bats is a constant threat in the Amazonian region, regularly exceeding in fatalities the classical dog transmitted rabies in recent years. In 2004-5, several outbreaks have occurred in Para, Brazil. In May-June 2005, following 15 deaths, mostly children, in Augusto Correa, a rural community of 53,000 people dispersed along the Amazon estuary, 3,500 subjects aged from 2 to 60 years received purified Vero cell rabies vaccine (PVRV Verorab®, Sanofi Pasteur, France) for post- or pre-exposure prophylaxis. The presentation will summarize the follow-up of this community during 4 years after vaccination. The persistence of anti-RABV neutralizing antibodies (VNAbs) levels was evaluated by RFFIT, FAVN, and Platelia ELISA (Bio- RAD®) against the PV and CVS reference strains as well as a vampire bat isolate. Subjects with VNAb levels <0.5 IU(EU)/mL were boosted. From a total of 507 subjects included in the study, 428 (84.4%) were available all along the follow-up, an excellent adherence considering the isolation, dispersion, and nomadic live of the community. Remarkably, 5% to 7% of the surveyed population were potentially reexposed one to several times each year through animal bites (mainly dogs also bats, cats, monkeys). The persistence of the WHO minimum “seroprotective” level of VNAbs (≥0.5 IU/mL) four years after vaccination was observed in 85.8% of the non boosted population (346 patients). Interestingly, no statistical difference in VNAb persistence profiles were observed in pre-exposure (45 subjects) and post-exposure (301 subjects) treated populations. Globally, the VNAb level and persistence were better in young population than in elderly, and in females than in males, particularly the 16–40 years old males which showed lower GMT and seroprotection rates. No interference was observed between anti-malaria treatment and PVRV immunogenicity. At the methodological level, RFFIT and FAVN results appeared highly concordant. The concordance was lower with the ELISA results that showed a global increase in GMT value over the years paralleled by a decrease in statistical correlation with RFFIT (Pearson’s correlation coefficient = 0.82 in 2007 to 0.42 in 2009). A hundred serum samples were selected randomly each year to evaluate the concordance of RFFIT results using the PV strain versus a local vampire bat isolate. In summary, this study demonstrated persistence of anti-rabies VNAbs in the vast majority of vaccinees (PVRV Verorab ®) from this community at repeated risk of vampire bat bites.